Pengaruh Indeks Pembangunan Manusia Terhadap Kemiskinan di Provinsi Sumatera Utara - Sanjiwan Pasaribu; Abdul Jalil Akbar; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The problem that almost every developing country faces is poverty, and Indonesia is no exception. The root of the problem of poverty is that people cannot live properly. This has an impact on the quality of human resources, thereby reducing productivity and lowering the income of the community itself. Community income, unemployment, health, education and environmental conditions are factors that influence the occurrence of poverty problems. The poverty rate in North Sumatra is still relatively high compared to other regions, but North Sumatra is not included in the 10 poorest areas in Indonesia. Analyzing the effect of HDI on poverty is the aim of this study. This study uses simple regression for the research method and is processed using the help of SPSS 26 software. Through this study it can be seen that HDI has a significant effect on poverty in North Sumatra.